(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
With cybercrime increasing by 600% during the COVID-19 pandemic, the demand for cybersecurity professionals has also risen significantly. There are roughly 700,000 unfilled cybersecurity positions that continue to affect businesses and have the potential to cause significant problems. Education for novice cybersecurity students suffers from teaching materials not being practical, modern, nor intuitive enough to inspire these students to pursue a career in the cybersecurity field. In this paper, we present our methodology and create a module for teaching the basics of software security using Armitage and Metasploit. We design our module and hands-on labs using a preconfigured Windows 10 VM, a Metasploitable VM and a Kali Linux VM with custom-made tools. Our methodology and module is validated through the results of a GenCyber high school cybersecurity camp. The module is available at GitHub.